2021
DOI: 10.1097/md.0000000000023953
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupuncture on childhood attention deficit hyperactivity disorder

Abstract: Introduction: The purpose of this paper is to evaluate the efficacy and safety of acupuncture in the treatment of childhood attention deficit hyperactivity disorder (ADHD). Methods and analysis: We will electronically search PubMed, Medline, Embase, Web of Science, the Cochrane Central Register of Controlled Trial, China National Knowledge Infrastructure, China Biomedical Literature Database, China Science Journal Database, and Wan-fang Database from their inception. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Another, similar review identified nine main channels that contribute to autism symptoms [ 35 ]. The increasing number of protocol-type articles shows that research designs in this field have become more rigorous and scientific, consistent with the rapid development of evidence-based medicine in recent years [ [36] , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 94%
“…Another, similar review identified nine main channels that contribute to autism symptoms [ 35 ]. The increasing number of protocol-type articles shows that research designs in this field have become more rigorous and scientific, consistent with the rapid development of evidence-based medicine in recent years [ [36] , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 94%
“…Over the past few decades, different treatments and interventions aimed at inattention, hyperactivity, and impulsivity have been used. Medications, including methylphenidate, amphetamine, atomoxetine, and guanfacine, have been widely used in the acute treatment of ADHD (Van Doren et al., 2019) and reported to be effective for some features in short‐term (Lin et al., 2021); however, medications failed to improve mood, self‐esteem, and social relationships (Harpin et al., 2016). Furthermore, the compliance of ADHD patients generally decreases after one year's medications (Frank et al., 2015).…”
Section: Introductionmentioning
confidence: 99%